2023
DOI: 10.1111/gcb.16871
|View full text |Cite|
|
Sign up to set email alerts
|

Ecosystem type drives soil eukaryotic diversity and composition in Europe

Abstract: Soil eukaryotes play a crucial role in maintaining ecosystem functions and services, yet the factors driving their diversity and distribution remain poorly understood. While many studies focus on some eukaryotic groups (mostly fungi), they are limited in their spatial scale. Here, we analyzed an unprecedented amount of observational data of soil eukaryomes at continental scale (787 sites across Europe) to gain further insights into the impact of a wide range of environmental conditions (climatic and edaphic) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…We assessed drivers of 41 European earthworm species and predicted the current and future distributions of 19 highly recorded species. Soil pH, phosphorus, and temperature were identified previously as strong drivers of earthworm distribution (Köninger et al, 2023;Phillips et al, 2019;Ruiz et al, 2021); however, we found precipitation seasonality, agricultural land area, and soil texture similarly or even more important for predicting patterns of earthworm distribution and richness (Figure 2b, Supporting Information Appendices S6-S8). The majority of the species occurred in the west of central Europe (i.e., the British Isles, Germany, the Netherlands, and Belgium) (Figure 2a).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…We assessed drivers of 41 European earthworm species and predicted the current and future distributions of 19 highly recorded species. Soil pH, phosphorus, and temperature were identified previously as strong drivers of earthworm distribution (Köninger et al, 2023;Phillips et al, 2019;Ruiz et al, 2021); however, we found precipitation seasonality, agricultural land area, and soil texture similarly or even more important for predicting patterns of earthworm distribution and richness (Figure 2b, Supporting Information Appendices S6-S8). The majority of the species occurred in the west of central Europe (i.e., the British Isles, Germany, the Netherlands, and Belgium) (Figure 2a).…”
Section: Discussionmentioning
confidence: 50%
“…Although the identified drivers of and predicted distributions for the targeted species aligned with the relevant literature (Rutgers et al, 2016;Phillips et al, 2019;Köninger et al, 2023), evaluating the resulting potential distributions is more challenging and more prone to bias due to major geographic and taxonomic gaps (Guerra et al, 2020). More targeted and standardized sampling is needed especially in central and southern of Spain, southern of Portugal, Italy, and eastern European countries (Supporting Information Appendices S12 & S13) (Guerra et al, 2020).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Regarding soil biodiversity, YSRs contributed to the first ever assessment of soil biodiversity across Europe. The analysis of the largest European soil DNA dataset (Orgiazzi et al, 2022) showed how soil microbial communities were mainly explained by soil properties, especially pH (bacteria), and by vegetation cover (fungi), while soil animals were more associated with historical conditions in terms of climate and land use (Köninger et al, 2023; Labouyrie et al, 2023). YSRs also explored the role of soil biodiversity in policy cycles (Köninger et al, 2022) and the interactions of manure and soil biodiversity (Köninger et al, 2021).…”
Section: The Eu Soil Observatory and Collaborative Doctoral Partnersh...mentioning
confidence: 99%